Revealing the SIDA culture in Manggarai on an accrualbased accounting perspective - Leopold Melkiano Triangga Dawu; Susana Purnamasari Baso; Maria Odriana Veronica Moi (Universitas Hayam Wuruk Perbanas, 2022)
From the point of view of accounting science, the culture of giving donations that causes a form of payment and occurs in community groups can refer to the recognition of transactions called the basis of accounting. The culture of paying between families in community groups has affected the structure of society itself. This study aims to examine the